(untitled) (International Journal of Tissue Repair, 2025)
Background: Diabetic foot ulcers (DFUs) are chronic wounds often marked by delayed epithelialization and limited response to standard of care (SOC) procedures. Their persistence substantially impairs quality of life and are associated with 50-60% infection rates and around 30% 5-year mortality rates, highlighting the need for new cost-effective strategies. Methods: This case series evaluated two subjects with chronic DFUs evaluated at 2 sites between April 2025 and July 2025. Offloading was provided with a removable walker boot. Subjects had target ulcers between >1.0 cm2 and 20.0 cm2 at enrollment that had not closed after 4 weeks of SOC. Subjects received a weekly application of a full-thickness placental membrane allograft (FT; caregraFT™, Tiger Wound Care Medical, LLC, Conshohocken, PA, USA) combined with standard care (sharp debridement, offloading, and moisture balance) in an ongoing randomized con-trolled modified platform trial. Results: The two patients were between the ages of 79 and 86, one female and one male. One patient reached ≥50%, ≥75%, and ≥90% PAR by Weeks 1, 3, and 6, respectively, with complete closure at Week 9. The other subject reached ≥50%, ≥75%, and ≥90% PAR by Weeks 2, 4, and 5, respectively, with complete closure at Week 8. Both wounds were confirmed closed in subsequent closure confirmation visits. No product related adverse events were reported. Conclusion: These cases demonstrate the potential of FT allografts in aiding SOC to improve wound closure rates of DFUs in older patients with both hard-to-heal and newly diagnosed chronic wounds. These results highlight the importance of continued clinical evaluation through controlled studies aimed at confirming both the wound care benefits and the potential for reducing overall healthcare costs.